Do stroke services still show sex differences? A multicenter study - Nahas, Nevine El; Shokri, Hossam; Roushdy, Tamer; Dawood, Noha; Zaki, Amr; Farhoudi, Mehdi; Hokmabadi, Elyar Sadeghi; Al Hashmi, Amal; Brola, Waldemar; Kosno, Krystian; Falup-Pecurariu, Cristian; Ciopleias, Bogdan; et al. (Springer Science and Business Media LLC, 2023)
Background The issue of sex differences in stroke has gained concern in the past few years. However, multicenter studies are still required in this field. This study explores sex variation in a large number of patients and compares stroke characteristics among women in different age groups and across different countries. Methods This multicenter retrospective cross-sectional study aimed to compare sexes regarding risk factors, stroke severity, quality of services, and stroke outcome. Moreover, conventional risk factors in women according to age groups and among different countries were studied. Results Eighteen thousand six hundred fifty-nine patients from 9 countries spanning 4 continents were studied. The number of women was significantly lower than men, with older age, more prevalence of AF, hypertension, and dyslipidemia. Ischemic stroke was more severe in women, with worse outcomes among women (p: < 0.0001), although the time to treatment was shorter. Bridging that was more frequent in women (p:0.002). Analyzing only women: ischemic stroke was more frequent among the older, while hemorrhage and TIA prevailed in the younger and stroke of undetermined etiology. Comparison between countries showed differences in age, risk factors, type of stroke, and management. Conclusion We observed sex differences in risk factors, stroke severity, and outcome in our population. However, access to revascularization was in favor of women.